Shocks of government bonds and yield impact economic growth in South Africa - Olebogeng Petlele; Eugene Msizi Buthelezi (Cogent Economics & Finance)
This study investigates the dynamic relationship between government bonds, bond yields, and economic growth in South Africa, utilizing Structural Vector Autoregression (SVAR) analysis on time series data from 1986 to 2024. Despite the extensive literature on government bonds and economic growth, a significant gap remains in understanding the differential impacts of bond maturities and yield shocks on GDP growth, particularly in the context of emerging markets like South Africa. The findings reveal that shocks to short-term government bonds initially lead to a decline in GDP growth due to crowding out effects, while shocks to mid-term government bonds produce a ‘W-shaped’ effect on growth. Additionally, shocks to short-term bond yields result in a sharp decline in GDP, whereas long-term bond yield shocks lead to an initial decline followed by a subsequent increase in growth. These results emphasize the importance of considering bond maturity and yield differences when assessing their economic impact. Policymakers are advised to maintain stable and predictable monetary and fiscal policies to minimize uncertainty in interest rate movements and borrowing costs. This study addresses the existing research gap by providing a nuanced understanding of the interactions between bond market dynamics and economic growth in South Africa.